Accuracy evaluation of computer-designed surgical guide template in oral implantology. Issue 10 (December 2015) - Shen, Pei; Zhao, Jingyang; Fan, Linfeng; Qiu, Hanxuan; Xu, Weifeng; Wang, Yanhui; Zhang, Shanyong; Kim, Yong-Jin
Abstract: Objective: The purpose of this study was to assess the accuracy of implant placement using surgical guide templates, and to compare the results with implant placement based on computer-aided design (CAD) planning merely. Material and methods: A total of 60 patients with dentition defects were included in our study, who were equally divided into group I and group II. Preoperative cone beam computed tomography (CBCT) was performed and preoperative planning was designed with Simplant software for all 60 patients. A total of 52 implants were placed in group I patients based on the preoperative planning without surgical guide templates. Implant surgical guide templates for group II patients were designed and produced by a rapid prototyping (RP) technique. A total of 57 implants were inserted in group II patients with the assistance of surgical templates. Postoperative CBCT was performed for all 60 patients. Image registration was carried out between postoperative CBCT data and that of preoperative planning data. Deviations of the implant between the actual and planned positions were measured and compared. Results: There was no significant structure damage during the surgery. Osseointegration was achieved in all implants, and both soft and hard tissues around implants were stable. Variation at the implant shoulder in group II was 1.18 ± 0.72 mm, apex 1.43 ± 0.74 mm, angulation 4.21 ± 1.91 mm, and depth 0.54 ± 0.29 mm, whereas the variation in group I was 2.07 ± 0.51 mm (P < 0.01), 2.89 ± 1.02 mm (P < 0.01), 8.84 ± 4.64 mm (P < 0.05), and 0.78 ± 0.33 mm (P > 0.05). Conclusion: The use of surgical guide templates can achieve higher precision and accuracy in implant shoulder, apex, and angulation, which is much more suitable for complicated procedures and conditions such as the flapless method, immediate loading, aesthetic restoration, and insufficient bone height.